Pembuatan Program Aplikasi Laporan Perawatan Korektif Laboratorium Pemesinan Polman Babel - Zaldy Sirwansyah Suzen; Indra Feriadi (Manutech : Jurnal Teknologi Manufaktur, 2018)
Politeknik Manufaktur Negeri Bangka Belitung is university that provide education and training in the field of engineering where there are machinery and equipment as a means of learning. The good maintenance of machine and equipment is the most important to support the learning activities. However the bad maintenance will cause disadventages for company benefit. During this time corrective maintenance is handled in a manual that is recorded in books that causes data repairing of machine is not documented well. Based on this improvement and maintenance of existing system development should be pursued in order to improve the administration system of care maintenance. The system design is oriented for creation of database applications that are expected to solve the problem.